Administrative Empowerment as a Modern Approach to achieve a Service Quality in Business Organizations Field study on Algeria Telecom institution - Rachame, Kahina; Jamile, Ahmed (Milev Journal of Research and Studies, 2017)
This study seeks to try and find out the contribution of managerial empowerment in achieving service quality, and in order to test the Algerian environment to embrace these new concepts has been chosen Algerian Telecom company as a location of research, and to achieve the objectives of the study we designed and developed two questionnaires, one was directed to the employees of Algerian Telecom company, in order to determine the level of empowerment in the company, and the other to its customers in order to identify the relationship between two variables and to find out the quality level of service that provided by the company under study, were used Statistical Package for Social Sciences (SPSS) to analyze the questionnaire data, the study found there is no role for the mpowerment in service quality, The study recommends the need to increase attention to the company employees, opening a wider freedom of action and hear their ideas and suggestions, With the face of obstacles that limit the effective implementation of empowerment, such as centralized, and hierarchical organizational structures and complex, And take more attention to customers, What leads one way or another to improve the service quality at the company under study.